POLA PERSEBARAN KERUANGAN EROSI PERMUKAAN SEBAGAI RESPON LAHAN TERHADAP HUJAN DI DAERAH ALIRAN SUNGAI SECANG, KABUPATEN KULONPROGO, DAERAH ISTIMEWA YOGYAKARTA INDONESIA - , H. Suprapto Dibyosaputro, Drs.,M.Sc.; , Prof. Dr. Sutikno ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This dissertation is entitled with the âSpatial ditribution patterns of the surface erosion as respond of lands to the rain fall in Secang catchment area, Kulonprogo District, Yogyakarta Special Region, Indonesia. The aims of the research are 1). to study the rain and land parameters which are relevant as factors that act as predictor to the distant differences of starting locations of overland flow (JLP) as well as surface erosion (JEP), and starting periode of overland flow occurences (WEP) as well as starting periode of surface erosion (WEP), 2). to determine the greatest influence of once among the parameters of the land and rain on the difference of JLP and JEP, as well as WLP and WEP of the land, and 3). to analyse the spatial distribution patterns of those starting locations of JLP and JEP occurences measured from the hilly ridge of land. Survey method was used in this study to collect primary data, these are: soil humidity, soil permeability, soil texture, soil depth, and soil organic matter content, slope, tree height, land cover density, and rainfall intensity as the out proposed independent variables, as well as data of JLP, JEP, WLP and WEP as the dependent variables. Processing and data analysis using statistical analysis with multiple linear regression equation approach. The results showed that 1). Not all the parameters of the land and the rain were accepted as independent variables that effect to the JLP, JEP, WLP and WEP in multiple linear regression equation. The 9 (nine) parameters of the proposed land and rain, only 7 (seven) parameters are accepted as independent variables against the JLP